Damage detection in a post tensioned concrete beam – Experimental investigation. (1st December 2016) - Limongelli, M.P.; Siegert, D.; Merliot, E.; Waeytens, J.; Bourquin, F.; Vidal, R.; Le Corvec, V.; Gueguen, I.; Cottineau, L.M.
Highlights: Results of static and/or dynamic tests on a post tensioned concrete beam are reported to investigate the possibility to detect deterioration. The beam was tested in several configurations aimed to reproduce different phases of the 'life' of the beam. The effect of different test setup and types of testing, of the cracking and of the de-tensioning of the cables have been analyzed by following the evolution of the first modal frequency and of the bending stiffness. The correlation between the results of static and dynamic tests is investigated through the correlation of the values of the first modal frequency and the bending stiffness. Abstract: The paper deals with the results of an experimental campaign carried out on a post tensioned concrete beam with the aim of investigating the possibility to detect early warning signs of deterioration based on static and/or dynamic tests. The beam was tested in several configurations aimed to reproduce 5 different phases of the 'life' of the beam: in the original undamaged state, under increasing loss of tension in the post tensioning cables, during and after the formation of cracks at mid span, after a strengthening intervention carried out by means of a second tension cable, during and after the formation of further cracks on the strengthened beam. Responses of the beam were measured by an extensive set of instruments consisting of accelerometers, inclinometers, displacement transducers, strain gauges and optical fibers. In this paper data from accelerometers and displacement transducers have been exploited. The paper presents the test program and the dynamic characterization of the beam in the different damage scenarios in terms of the first modal frequency, identified from dynamic tests and of the bending stiffness monitored during static tests.